Effects of Three Music Therapy Interventions on the Verbal Expressions of Children With Autism Spectrum Disorder: A Combined Single-Subject Design - Attar, Nayla; Al-Hroub, Anies; El Zein, Farah (Frontiers in Psychology, 2022)
The specific aims of this research study were to (a) examine the differential effect of three different music interventions, namely the interactive music playing therapy (‘music and singing’), interaction music singing therapy (‘singing’), and receptive music therapy (‘listening’) studying the varying latency periods in the response time it took three-year-old children diagnosed with Autism Spectrum Disorder to elicit the target word vocally; and (b) assess the index of happiness of children with ASD after the implementation of the three music interventions, which can, in turn, be used to influence their overall quality of life through this specific intervention. This study used a combined single-subject research design consisting of delayed multiple baseline across the participants and a multielement design to compare the effects of each music intervention technique targeting the child’s verbal response during playback of a practiced song. Findings demonstrated ‘singing’ to be associated with the lowest latency compared to the other two interventions (‘listening’ and ‘singing and music’) across participants. Additionally, happiness levels varied from neutral to happy, signifying an overall positive experience during participation in the music ABA intervention.